SEMANTIC APPROACHES IN ISLAMIC STUDIES; THE REVIEW OF TOSHIHIKO IZUTSU’S THOUGHT - Muzaqqi Muzaqqi (PEDAGOGIK : JURNAL PENDIDIKAN, 2016)
In applying this approach in a study Toshihiko semantics tend to be very strict in using the analytical methods used. Each concept in a comprehensive manner with the concept of talking about his opponent, with reference to the Qur’an itself. Qur’an thus spoke and explained about himself. Excerpts from the pre-Islamic poetry describes in detail how historically a concept born, evolve and anticipated by the Qur’an.